The effect of sales growth and profitability on profit changes in pharmaceutical companies listed on the IDX in 2014-2021 - Suseno Hadi Purnomo; Rahmi Nur Islami; Kartini Kartini (Trigin Publisher, 2023)
This study aims to examine the effect of sales growth, and profitability, on profit changes in health companies listed on the Indonesia Stock Exchange in 2014-2021. The goal and hope of a company is to try to achieve changes in profits that increase each period. This creates a problem because of the phenomena in the field, changes in profit fluctuate every year. So that it can raise the question of what factors can affect fluctuations in changes in earnings. Based on previous research and the data above, this study tries to include sales growth, profitability as one of the variables that affect changes in profits. The population of this study is health companies listed on the Indonesia Stock Exchange in 2014-2021. The number of samples used in this study were 8 health sector companies obtained by purposive sampling technique. Data collection techniques used are documentation and observation. The analytical tool used in this study is multiple regression analysis with the help of SPSS version 25.0. The results of this study indicate that sales growth and profitability as measured by net profit margin (NPM) have a positive and not significant effect on profit changes